Secret seven mystery - Blyton, Enid (Hodder and Stoughton Senenoakes, 1957)
A girl has mysteriously run away from home, and her parents are frantic with worry. Can the Secret Seven follow the clues and catch up with the girl - or will Susie, Jacks troublesome little sister, get in the way? -- back cover